2012
DOI: 10.3348/kjr.2012.13.4.403
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between Symptomatic and Asymptomatic Extraforaminal Stenosis in Lumbosacral Transitional Vertebra: Role of Three-Dimensional Magnetic Resonance Lumbosacral Radiculography

Abstract: ObjectiveTo investigate the role of lumbosacral radiculography using 3-dimentional (3D) magnetic resonance (MR) rendering for diagnostic information of symptomatic extraforaminal stenosis in lumbosacral transitional vertebra.Materials and MethodsThe study population consisted of 18 patients with symptomatic (n = 10) and asymptomatic extraforaminal stenosis (n = 8) in lumbosacral transitional vertebra. Each patient underwent 3D coronal fast-field echo sequences with selective water excitation using the principl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 17 publications
0
11
0
4
Order By: Relevance
“…The association of low back pains with LSTV, referred to as "Bertolotti's syndrome", is controversial. However, there may be symptoms originating from the degeneration of the anomalous articulation, facet joint arthrosis and nerve root compression between the broadened transverse process of the last lumbar segment and the sacral ala ( 3 , 12 , 13 ). Additionally, there are studies which reported increased incidences of disc degeneration and disc herniation above the LSTV ( 2 , 8 - 10 , 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…The association of low back pains with LSTV, referred to as "Bertolotti's syndrome", is controversial. However, there may be symptoms originating from the degeneration of the anomalous articulation, facet joint arthrosis and nerve root compression between the broadened transverse process of the last lumbar segment and the sacral ala ( 3 , 12 , 13 ). Additionally, there are studies which reported increased incidences of disc degeneration and disc herniation above the LSTV ( 2 , 8 - 10 , 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…The causative factors for LDH include disc degeneration, trauma, and anatomical abnormalities such as lumbosacral transitional vertebrae (LSTV). LSTV, which includes sacralization or lumbarization at the lumbosacral junction, has been recognized as a causative factor for LDH and is associated with several problems, including an increased risk for advanced disc degeneration or disc herniation, altered nerve root direction or functioning, facet joint arthrosis,, and concomitant cervical ribs . Although some studies have evaluated the clinical impact of LSTV, few have attempted to determine an effective conservative treatment method for LDH presenting concurrently with LSTV, and none have evaluated whether the presence of LSTV influences the therapeutic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…These radiographic findings were distinctively absent in cases of asymptomatic extraforaminal stenosis. 82 Resection of a right-sided unilateral anomalous lumbosacral articulation provided 90% relief of left low back pain and complete relief of left leg symptoms in 1 patient with a contralateral symptomatic L6-S1 facet joint. The authors suggested that the patient's pain was not associated with the anomalous articulation itself, but was probably due to additional stress placed on the normal contralateral joint.…”
mentioning
confidence: 99%